PENGUATAN KARAKTER PROFIL PELAJAR PANCASILA MELALUI INTEGRASI NILAI-NILAI ISLAM DI KELAS 4 SEKOLAH DASAR - Afifa Yusriza; Ajeng Nur Afifah; Anisa Puspita Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The Pancasila Student Profile is a national education goal directed at fostering the character of students in Indonesia which must be realized by all parties through six main elements, namely 1) faith, devotion to God Almighty, and noble character, 2) independence, 3) cooperation, 4) global diversity, 5) critical reasoning, and 6) creativity. This research is a library research by analyzing the values of Islamic Religious Education on the profile of Pancasila students. Data collection techniques through library data through the process of reading, recording, analyzing and processing the formulation of problems in the study. The results showed that the Pancasila Student Profile is in line with the values of Islamic Religious Education which are divided into three aspects, namely. the value of faith, moral values and sharia values. The integration is as follows: the dimension of faith, piety to God Almighty, and noble character and integration with the value of faith, moral values integrated with the value of aqidah values, moral values; the dimension of independence, cooperation and creativity combined with moral values; The dimension of critical reasoning integrated with the value of faith and the dimension of global diversity integrated with sharia values.